FoMO living behavior in Islamic perspective: Case study of JKT48 fans - Syarifah, Siti Alfaini; Harahap, Muhammad Ikhsan; Daulay, Aqwa Naser (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2024)
Fear of Missing Out (FoMO) living behavior and JKT48 fan behavior are examined in this study. The research examines how FoMO living affects JKT48 members' financial choices and how Islamic principles affect their financial management. Qualitative phenomenological research is used. Interviews with JKT48 fans, the study subjects, are used to acquire data about Islamic FoMO living habits. Purposive sampling identified informants, and interviews, observations, and documentation gathered data. Data reduction, presentation, and conclusions were performed on the gathered data. The results indicated that 7 out of 10 informants did not display FoMO behavior, but 50% of female informants did. Around half of the informants, mainly women, were impacted by JKT48 fan group social interactions. This research found that most informants did not match theoretical FoMO indications. Impulsive decision-making, social pressure, and a need to remain connected are FoMO signs. Islam emphasizes moderation and self-control to prevent excessive conduct in FoMO life. Thus, imformants who can control FoMO-related impulsivity are Islamic. Public interest statements Most informants in this study needed to meet the theoretical research's FoMO indicators. Social desires, needing to be connected, and impulsive decision-making are FoMO symptoms. Islam promotes modesty and self-control to avoid FoMO excess. Informed parties that avoid FoMO-related impulsivity follow Islamic values.